Natural Products and Cancer Stem Cells - Marucci, Cristina; Fumagalli, Gaia; Calogero, Francesco; Silvani, Alessandra; S. Christodoulou, Michael; Martinet, Nadine; Passarella, Daniele (Current Pharmaceutical Design, 2015)
The development of modern technologies casts a new light on the natural products as an invaluable source of lead compounds that could guide drug discovery. Cancer stem cells are a subpopulation of cancer cells with a high clonogenic capacity and the ability to reform the parental tumours upon transplantation. They have been proposed to drive tumorigenesis and metastases. In this review, we present the ability of forty-nine different natural products to influence the biology of cancer stem cells.
Keywords: Natural products